2020
DOI: 10.21005/asp.2019.18.4.03
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of body type evaluation of different color variants of farmed mink (Mustela vison Sch.) against current evaluation standard

Abstract: The aim of the study was to comparatively analyze the body type traits in mink of different color variants, over a period of a few years, compared against the current mink evaluation standard. The mink were managed on mink farms located in northwestern Poland. The analysis covered the years 2011-2018. A statistically significant effect of color variant, year of assessment and farm, on which the license took place, was found. The highest average grades for the type were achieved by the mink in 2014, while the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The mortality rate of young mink during the period of maternal nursing ranges from 13 to as much as 27% [Lagerkvist et al 1994], and the highest mortality is recorded in the first week after birth [Felska-Błaszczyk 2021]. The survival rate of the young is determined by many factors, including color variety, age of the mother, and litter size Kołodziejczyk 2006, Kołodziejczyk andSocha 2012]. Schou and Malmkvist [2017] and Seremak et al [2013] found that litters that were too numerous had a higher mortality rate than litters that were less numerous, which was due to the fact that pups in larger litters (more than 9 young) are much smaller and the mother has limited feeding capacity.…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate of young mink during the period of maternal nursing ranges from 13 to as much as 27% [Lagerkvist et al 1994], and the highest mortality is recorded in the first week after birth [Felska-Błaszczyk 2021]. The survival rate of the young is determined by many factors, including color variety, age of the mother, and litter size Kołodziejczyk 2006, Kołodziejczyk andSocha 2012]. Schou and Malmkvist [2017] and Seremak et al [2013] found that litters that were too numerous had a higher mortality rate than litters that were less numerous, which was due to the fact that pups in larger litters (more than 9 young) are much smaller and the mother has limited feeding capacity.…”
Section: Introductionmentioning
confidence: 99%